Generations of Business Information, 1937-2012: Moving from Data Bits to Intelligence. - Gross, Andrew; Solymossy, Enteric (Information & Culture, 2016)
In this article, we investigate the collection, organization, and dissemination of business information during the past seventy-five years. Transforming millions of "data bits" to intelligence for better decision making remains a challenge. However, we have come a long way since the late 1930s by building databases, connecting nodes and networks, and constantly upgrading the quality of business information. Classification schemes, search techniques, retrieval methods, delivery speed, and storage capacity have all increased exponentially. The key forces contributing to such transformation were public-private cooperation, the dedication of pioneers who "grew the field," and the entrepreneurial ventures of data consolidators and research agencies. The social, economic, and organizational forces brought about changes that were coupled widi the requisite technology; diis paved the way for the creation of the Internet, the World Wide Web, and many related features that range from mobile communication to visualization techniques.